Analiysis of Phytoplankton Diversity on the Productivity of Vannamei Shrimp (Litopenaeus vannamei) Intensive Pond, Jatisari Village, Banyuwangi - Juliyanto, Nabilla Anggi; Maftuch, Maftuch; Masithah, Endang Dewi (Graduate School, Universitas Brawijaya, 2021)
Phytoplankton can be used to estimate the potential for vannamei shrimp production. It can be used as a provider of nutrient sources and has an important role in improving water quality. This study aims to analyze the phytoplankton community structure on the productivity of intensive vannamei shrimp ponds. The research was conducted in Jatisari Village, Banyuwangi, East Java, Indonesia. Carried out parameters were the calculation of density, phytoplankton diversity index, culture performance (SR, FCR, ADG), and water quality (temperature, water transparency, salinity, pH, DO, NO2, NO3, PO4, NH4). The results showed that there were six classes and 33 genera from both ponds, Chlorophyceae (10 genera), Bacillariophyceae (8 genera), Cyanophyceae (9 genera), Dinophyceae (3 genera), Euglonophyceae (1 genus), Criptophyceae (1 genus). The index value of the two ponds shows moderate diversity, H 'pond 1 is 1.76, and pond 2 is 2.02. The two plots' cultivation performance was SR 92% and 80%, FCR 1.08 and 1.13, ADG 0.31 g.day-1 and 0.35 g.day-1, respectively. The physical and chemical parameters of the research showed a good enough value for the life of vannamei shrimp and phytoplankton.Keywords: Cultivation performance, Phytoplankton, Vannamei shrimp.